2007
DOI: 10.1354/vp.44-6-796
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Substance is “Not Amyloid” in the Mouse Nasal Septum

Abstract: An eosinophilic substance (ES) is usually observed in the mouse nasal septum and increases in volume with aging. It has been described as amyloid in textbooks and one report. However, it has been described as "not amyloid" in other reports because there was a negative reaction to Congo red. In this study, the ES was investigated histopathologically and electron microscopically to determine whether it was amyloid or not. The ES was only observed at the interstitium of clear HE-stained nasal glands in the septum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Furthermore, AM was not only very similar to the material in the rough endoplasmic reticulum of the clear HE-stained nasal gland epithelial cells, it was also connected to it. These findings suggested that the clear HE-stained nasal gland epithelial cells produced AM [1].It is not clear how AM produced by clear HE-stained nasal gland epithelial cells deposits in the interstitium. In this study, we investigated the deposition process histopathologically and electron microscopically.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Furthermore, AM was not only very similar to the material in the rough endoplasmic reticulum of the clear HE-stained nasal gland epithelial cells, it was also connected to it. These findings suggested that the clear HE-stained nasal gland epithelial cells produced AM [1].It is not clear how AM produced by clear HE-stained nasal gland epithelial cells deposits in the interstitium. In this study, we investigated the deposition process histopathologically and electron microscopically.…”
mentioning
confidence: 90%
“…ES deposited at the interstitium of the clear HEstained nasal glands only. Electron microscopically, AM was observed in the clear HE-stained nasal gland epithelial cells as well as in the interstitium [1]. Glands composed of nasal gland epithelial cells holding AM were also observed in areas without interstitial AM nearby.…”
mentioning
confidence: 91%
See 3 more Smart Citations